Professional Appearance dalam Suatu Budaya Organisasi: Seberapa Krusial untuk Kesuksesan Karir - Caecilia Tri Wahyanti (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This qualitative study explores the role of professional appearance within organizational culture and its impact on career success and personal branding. Unlike previous research, this study analyzes professional appearance and its influence across various sectors and professions—ranging from services and commerce to manufacturing, from hoteliers, bank frontliners, PR professional, marketing people, to lawyer. Involving ten informants from diverse industries, the study finds that professional appearance is described differently and is crucial for career success of those client-facing roles but is considered less important for positions that do not involve direct external interaction. Appearance standards vary from formal to smart casual, reflecting unique organizational values. Despite a post-pandemic shift in styles, managing one's appearance remains vital for establishing credibility and self-confidence. The findings indicate that employees generally accept appearance regulations, with attitude and non-verbal communication serving as key elements in impression management and career success.